AP-1 (Activated Protein-1) Transcription Factor JunD Regulates Ischemia/Reperfusion Brain Damage via IL-1β (Interleukin-1β). Issue 2 (February 2019) - Diaz-Cañestro, Candela; Reiner, Martin F.; Bonetti, Nicole R.; Liberale, Luca; Merlini, Mario; Wüst, Patricia; Amstalden, Heidi; Briand-Schumacher, Sylvie; Semerano, Aurora; Giacalone, Giacomo; Sessa, Maria; Beer, Jürg H.; et al.
Abstract : Background and Purpose—: Inflammation is a major pathogenic component of ischemia/reperfusion brain injury, and as such, interventions aimed at inhibiting inflammatory mediators promise to be effective strategies in stroke therapy. JunD—a member of the AP-1 (activated protein-1) family of transcription factors—was recently shown to regulate inflammation by targeting IL (interleukin)-1β synthesis and macrophage activation. The purpose of the present study was to assess the role of JunD in ischemia/reperfusion-induced brain injury. Methods—: WT (wild type) mice randomly treated with either JunD or scramble (control) siRNA were subjected to 45 minutes of transient middle cerebral artery occlusion followed by 24 hours of reperfusion. Stroke size, neurological deficit, plasma/brain cytokines, and oxidative stress determined by 4-hydroxynonenal immunofluorescence staining were evaluated 24 hours after reperfusion. Additionally, the role of IL-1β was investigated by treating JunD siRNA mice with an anti–IL-1β monoclonal antibody on reperfusion. Finally, JunD expression was assessed in peripheral blood monocytes isolated from patients with acute ischemic stroke. Results—: In vivo JunD knockdown resulted in increased stroke size, reduced neurological function, and increased systemic inflammation, as confirmed by higher neutrophil count and lymphopenia. Brain tissue IL-1β levels were augmented in JunD siRNA mice as compared with scramble siRNA, whereas no difference was detected in IL-6, TNF-α (tumor necrosis factor-α), and 4-hydroxynonenal levels. The deleterious effects of silencing of JunD were rescued by treating mice with an anti–IL-1β antibody. In addition, JunD expression was decreased in peripheral blood monocytes of patients with acute ischemic stroke at 6 and 24 hours after onset of stroke symptoms compared with sex- and age-matched healthy controls. Conclusions—: JunD blunts ischemia/reperfusion-induced brain injury via suppression of IL-1β. Abstract : Supplemental Digital Content is available in the text.